Longitudinal association between sleep quality and fatigue during pregnancy: an observational cohort study - Zhanhong Fan; Shuhan Yan; Li Sun; Zhiqiu Cao; Huahua Liu; Akinyemi Lydia Idowu; Bin Zhu; Feng Zhang (BMC Psychiatry)
Abstract Objective The bidirectional relationship between the trajectories of change in sleep quality and fatigue during pregnancy remains unclear. Methods 626 pregnant women were included in the final analysis. The fatigue Scale designed by Chalder assessed fatigue. Pittsburgh Sleep Quality Index was used to evaluate the sleep quality of pregnant women at T1, T2, T3 and T4. Growth mixture modeling characterized sleep quality trajectories during pregnancy in three groups (Group1: Consistently poorer sleep quality group in third trimester of pregnancy; Group2: Consistently poorer sleep quality group in second trimester of pregnancy; Group3: Stable sleep group). Generalized Estimating Equations were used to examine the relationship between different sleep qualities and fatigue in pregnant women. Latent growth curve models were also used to explore how the changes in sleep quality or fatigue during pregnancy affected their mutual trajectories. Results Results showed significant differences in fatigue among the three groups based on the trajectory of sleep quality(P = 0.004). Compared with group3(stable sleep group), group 2(consistently poorer sleep quality group in second trimester) exhibiting the highest level of total fatigue, next was group1(consistently poorer sleep quality group in third trimester of pregnancy). The results of the time-invariant covariate and time-variant covariate LGCM showed that sleep quality and fatigue during pregnancy mutually influenced each other within specific gestational windows. The parallel LGCM results indicated that the initial levels of sleep quality and fatigue were correlated (r = 1.666, P < 0.001), and the initial level of sleep quality predicted the trajectory of fatigue changes (β = 0.202, P = 0.001). Similarly, the initial level of total fatigue during pregnancy was also associated with sleep quality but could not predict the trajectory of sleep quality. Conclusion There was a two-way connection between sleep quality and fatigue in pregnant women, underscoring the importance of comprehensive management and intervention for poor sleep quality or excessive fatigue during pregnancy. Trial registration number ChiCTR2100053966, 04/12/2021.